2005
DOI: 10.1002/cbic.200400247
|View full text |Cite
|
Sign up to set email alerts
|

Malassezin, a Novel Agonist of the Aryl Hydrocarbon Receptor from the Yeast Malassezia furfur, Induces Apoptosis in Primary Human Melanocytes

Abstract: Pityriasis versicolor is the most common skin mycosis in humans worldwide. Yeasts of the genus Malassezia, particularly M. furfur, a saprophyte occurring widely on human skin, are generally regarded as the causative agents. Pityriasis versicolor is often accompanied by a long-lasting depigmentation that persists even after successful antimycotic therapy. M. furfur is able to convert tryptophan into a variety of indole alkaloids, some of them showing biological properties that correlate well with certain clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…More specifically, a dose-dependent induction of apoptotic markers after the cultivation of melanocytes with malassezin for 24 h was reported. It was also observed that the biosynthesis of melanin is also reduced in a similar dose-dependent way (184). However, the reduction in the level of melanin is most probably due to the apoptosis of melanocytes, and it is not the result of a specific activity on the biosynthetic pathway of melanin.…”
Section: Malassezia-produced Ahr Ligands and Significance Of Ahr Actimentioning
confidence: 72%
See 3 more Smart Citations
“…More specifically, a dose-dependent induction of apoptotic markers after the cultivation of melanocytes with malassezin for 24 h was reported. It was also observed that the biosynthesis of melanin is also reduced in a similar dose-dependent way (184). However, the reduction in the level of melanin is most probably due to the apoptosis of melanocytes, and it is not the result of a specific activity on the biosynthetic pathway of melanin.…”
Section: Malassezia-produced Ahr Ligands and Significance Of Ahr Actimentioning
confidence: 72%
“…However, conventional culture and identification methods offer the advantage of further evaluating the isolates for possible virulence factors, such as the production of phospholipase (44,170) and indole (108,184,336) and melanin synthesis (107). Furthermore, this was highlighted in a study by Akaza et al (6), in which the seasonal rates of isolation of Malassezia species from healthy skin determined by quantitative PCR (qPCR) were compared with those determined by use of Leeming-Notman agar (197).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tryptophan metabolites from malassezia yeast induce apoptosis in human melanocytes, which leads to depigmentation of the skin (pityriasis versicolor) [104]. Imiquimod, an immune response modifier that stimulates cytotoxic T-cell-mediated responses through activation of toll-like receptors, leads to tumor destruction and depigmentation in lentigo-maligna lesions [105,106].…”
Section: Biological Effectorsmentioning
confidence: 99%